Effects of simultaneous CO2 addition and biomass recycling on growth characteristics of microalgal mixed culture. Issue 12 (21st September 2021) - Fallahi, Alireza; Hajinajaf, Nima; Tavakoli, Omid; Mehrabadi, Abbas
Abstract: BACKGROUND: This study aims to investigate the effect of simultaneous carbon dioxide (CO2 ) addition and biomass recycling on specific performance parameters (including biomass productivity and harvestability, and species abundance) of the mixed culture of two freshwater microalgae species Chlorella vulgaris and Scenedesmus obliquus in a flat‐panel photobioreactor grown semicontinuously using secondary effluent urban wastewater as the culture medium. Recycling a portion of the gravity‐harvested biomass back to the system has positive effects on biomass productivity and harvestability by letting microalgal cells utilize more of the available light energy and promoting the dominance of settleable microalgal species of S. obliquus (owing to their large cell sizes) in the mixed culture. Furthermore, CO2 addition could supply the carbon limitation of urban wastewater and boost biomass production. RESULTS: The work confirmed that simultaneous CO2 addition and biomass recycling improved the biomass productivity by 314%, promoted the dominance of the larger algae species S. obliquus in the mixed culture by 38%, and increased the gravity sedimentation by 85% compared to the control that had no recycling and CO2 addition. Concerning the secondary effluent urban wastewater, the interaction of CO2 addition and biomass recycling was insignificant regarding the improvement in nutrient removal efficiency. CONCLUSION: The findings proved the potential benefits of simultaneous biomass recycling and CO2 addition for reaching a high cell density, and demonstrated its potential for high biomass harvest efficiency in microalgae‐based wastewater treatment systems. © 2021 Society of Chemical Industry (SCI).